Effect of Organizational Justice on Turnover Intention: Mediating Role of Employee Motivation - MUHAMMAD YOUNAS; IMRAN SAEED; GHAYYUR QADIR; SAIF ULLAH KHAN (Journal of Business & Tourism, 2021)
Turnover is a substantial problem all over the world, in all the industries. The problem is further impairing to the performance of knowledge intensive industries such as pharmaceuticals. This study examined the effect of Organizational justice facets i.e. Procedural Justice, Distributive Justice and Interactional Justice on Turnover Intention. Based on a sample of 141employees from 19 Private sector pharmaceutical companies located in Peshawar. The results reveal that Procedural Justice and Distributive Justice have significant and constructive effect on Turnover Intention while of Interactional Justice had no statistically significant effect. The analysis also shows that Intrinsic and Extrinsic Motivation as mediating variables significant effect on relationship between Organizational and Turnover Intentions.